Metabolic perturbations in cardiomyopathies: implications for early diagnosis and targeted interventions - Al-Shahrabi, Rula; Al Mansoori, Ghadeera; Al-Saffar, Muna; Akawi, Nadia (Frontiers in Cardiovascular Medicine, 2025)
Cardiomyopathy (CM) is a heterogeneous group of diseases characterized by structural and functional changes in the heart, with the exact cause often remaining unknown. CM can arise from both inherited and acquired metabolic disturbances. Alterations in energy production and substrate utilization impair the heart's contractile function and limit its ability to respond to stress. Given the complexity and dynamic nature of CM, as well as the multiple etiologies involved, we reviewed metabolomic studies employing high-throughput platforms to understand how metabolic pathways shift across CM subtypes and how these perturbations may inform clinical translation. Several recurring disruptions emerge across CM with alterations in amino acid metabolism (valine, leucine, methionine, tryptophan, tyrosine); mitochondrial redox imbalance (NAD/NADH shifts, niacinamide, acylcarnitines); and oxidative stress as central hallmarks. Each subtype, however, displays a different emphasis. For instance, hypertrophic CM is characterized by nucleotide remodeling, particularly in cases involving MYBPC3 mutations; dilated CM shows accumulation of Krebs cycle intermediates and trimethylamine-N-oxide; restrictive CM is associated with amino acid stress related to amyloidosis; tachycardia-induced CM involves fatty acid remodeling and elevated uric acid, while Takotsubo CM is linked to ketone utilization and glutamate excitotoxicity. Overall, a single metabolomic profile cannot capture CM. What emerges from this review is that subtype-specific shifts, and the way they interact, provide meaningful insight into disease mechanisms and highlight pathways with diagnostic, prognostic, and therapeutic relevance. This broader perspective shifts the focus beyond narrow comparisons, making the translational relevance of metabolomics in CM more apparent.